Who Cares? - A. C. Pritchard (Washington University Law Quarterly, 2002)
Jim Cox and Randall Thomas have identified an interesting phenomenon in their contribution to this symposium: institutional investors seem to be systematically “leaving money on the table” in securities fraud class actions. For someone who approaches legal questions from an economic perspective, the initial response to this claim is disbelief. As the joke goes, economists do not bend over to pick up twenty-dollar bills on the street. The economist knows that the twenty dollars must be an illusion. In a world of rational actors, someone else already would have picked up that twenty-dollar bill, so the effort spent bending over would be a waste. But Cox and Thomas provide persuasive evidence that the overwhelming majority of institutional investors cannot be bothered to file claims that would allow them to recover their share of the settlement in securities class actions. Should we care that institutional investors do not care? Cox and Thomas also make a persuasive case that institutional managers who fail to file claims in settled securities class actions are violating their fiduciary duties. Filing a claim is a purely ministerial task. Even if the settlement is modest, the return from filing the claim is likely to far exceed the costs. The question of compensation versus deterrence is not a purely academic one. Post-Enron, Congress is considering a variety of bills that would roll back the limitations imposed by the Private Securities Litigation Reform Act and expand the ability of investors to recover their losses through securities class actions. Legislators would do well to assess any such reform proposals against the standard of deterrence. Reforms geared toward enhancing compensation should be left on the table.
Keywords: Institutional investments; Class actions (Civil procedure); Securities; Class action settlements; Securities fraud